STUDI MORFOMETRIK DAN PENENTUAN UMUR IKAN LENCAM (Lethrinus lentjan) DI TEMPAT PELELANGAN IKAN (TPI) KETAPANG KOTA PANGKALPINANG - Siti Aisyah (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Otolith is used as one of the techniques to estimate the age of fish by looking at the annual otolith circle. Measuring the age of fish become an important aspect because its relevance to the growth and survival of fish. Database of fish age serve as one of basic information in effort management of fish resources in Bangka Island. This research was conducted in two stages; first is field sampling in TPI Ketapang – Pangkalpinang to sampling Lethrinus lentjan samples. Second is laboratory process for morphometric and age determination analysis. The result showed that the total calculation of morphometric characteristics of Lencam Fish (Lethrinus lentjan) is 23 characters. In morphometric characters, some of the total length and standard length of the fish samples are 25.5 cm and 21.5 cm. The age of Lencam Fish (Lethrinus lentjan) ranged from 1 - 3 years where the increasing length of fish body then the age of fish will increase until reach asimtot (saturated growth).